Contemporary Multi-modality Imaging of Prosthetic Aortic Valves - Bryan Q Abadie; Tom Kai Ming Wang (Reviews in Cardiovascular Medicine)
With the aging of the general population and the rise in surgical and transcatheter aortic valve replacement, there will be an increase in the prevalence of prosthetic aortic valves. Patients with prosthetic aortic valves can develop a wide range of unique pathologies compared to the general population. Accurate diagnosis is necessary in this population to generate a comprehensive treatment plan. Transthoracic echocardiography is often insufficient alone to diagnose many prosthetic valve pathologies. The integration of many imaging modalities, including transthoracic echocardiography, transesophageal echocardiography, cardiac computed tomography, cardiac magnetic resonance imaging, and nuclear imaging, is necessary to care for patients with prosthetic valves. The purpose of this review is to describe the strengths, limitations, and contemporary use of the different imaging modalities necessary to diagnose prosthetic valve dysfunction.